Convergence towards asymptotic state in 1-D mappings: a scaling investigation - Teixeira, Rivania M. N.; Rando, Danilo S. [UNESP]; Geraldo, Felipe C. [UNESP]; Costa Filho, R. N.; Oliveira, Juliano A. de [UNESP]; Leonel, Edson D. [UNESP] (Elsevier B.V., 2015)
Decay to asymptotic steady state in one-dimensional logistic-like mappings is characterized by considering a phenomenological description supported by numerical simulations and confirmed by a theoretical description. As the control parameter is varied bifurcations in the fixed points appear. We verified at the bifurcation point in both; the transcritical, pitchfork and period-doubling bifurcations, that the decay for the stationary point is characterized via a homogeneous function with three critical exponents depending on the nonlinearity of the mapping. Near the bifurcation the decay to the fixed point is exponential with a relaxation time given by a power law whose slope is independent of the nonlinearity. The formalism is general and can be extended to other dissipative mappings. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Scaling law; Critical exponents; Homogeneous function